A comprehensive analysis of binary mixtures as working fluid in high temperature heat pumps. (1st February 2023) - Abedini, Hamed; Vieren, Elias; Demeester, Toon; Beyne, Wim; Lecompte, Steven; Quoilin, Sylvain; Arteconi, Alessia
Highlights: An optimizer was developed to evaluate binary mixtures as refrigerant in heat pump. Three relevant cases with different sources/sink temperature profile were identified. For sensible sink/source cases binary mixtures improve the performance significantly. Binary mixtures can also reduce compression ratio and compressor outlet temperature. Water/ammonia is a suitable refrigerant once flammability is an issue in the process. Abstract: High-temperature heat pumps represent an emerging technology with a great potential in supplying clean heat to energy intensive industries. Suitable refrigerants for high-temperature heat pumps (up to 200 °C) have not been identified yet. This work aims to analyze the performance of binary mixtures as working fluid in high-temperature heat pumps delivering heat up to 200 °C with a special focus on zeotropic mixtures. Three relevant processes with different heat sources and sinks were selected to integrate the heat pump: latent/latent (e.g. distillation processes), latent/sensible (e.g. superheated steam drying), sensible/sensible (e.g. pressurized water production). To determine the best working fluid and cycle configuration for each process, an optimization framework was developed with the maximization of the coefficient of performance as objective function. For the first case with a latent heat sink and heat source, the best performing binary mixtures were near-azeotropic with slightly higher coefficient of performance compared to pure fluids. Moreover, binary mixtures provided several advantages such as the reduction of the compression ratio and compressor outlet temperature compared to pure fluids. A similar behavior was observed for the second case with a latent heat source and a sensible heat sink. For the third case with a sensible heat sink and heat source, binary mixtures resulted in a higher coefficient of performance (10 %) compared to pure fluids. Most of the best performing mixtures were hydrocarbons with high risk of flammability. Water/ammonia was the only mildly-flammable mixture among the top mixtures.